2014
DOI: 10.1501/egifak_0000001343
|View full text |Cite
|
Sign up to set email alerts
|

Views of academics on student selection criteria for graduate education

Abstract: The purpose of this study is to describe the views of academics about admission criteria to graduate education programs, who are working in the Social Sciences Institute and Educational Sciences Institute of Ankara University. Total of 274 academics employed in the Social Sciences Institution and Educational Sciences Institutions of Ankara University in the 2007-2008 school years participated in the study that is carried out on survey model. Participation levels of participants to some opinions about admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…When the literature is examined, it is observed that the concept of postgraduate education is defined in various ways. Postgraduate education is defined as the highest education institution where both the university's need for academics and society's need for qualified human resources and researchers are nurtured (Kayahan Karakul and Karakütük, 2014;Günay, 2018). With postgraduate education, highly qualified human resources, which are an important part of scientific and technological advancements and development, are cultivated (İbiş, 2014;Dikmen and Tuncer, 2016;Bayar and Çelenk, 2019;Koşar, Er, and Kılınç, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When the literature is examined, it is observed that the concept of postgraduate education is defined in various ways. Postgraduate education is defined as the highest education institution where both the university's need for academics and society's need for qualified human resources and researchers are nurtured (Kayahan Karakul and Karakütük, 2014;Günay, 2018). With postgraduate education, highly qualified human resources, which are an important part of scientific and technological advancements and development, are cultivated (İbiş, 2014;Dikmen and Tuncer, 2016;Bayar and Çelenk, 2019;Koşar, Er, and Kılınç, 2020).…”
Section: Introductionmentioning
confidence: 99%